Atypical association of Duane retraction syndrome and Bardet Biedl syndrome - Jethani Jitendra; Parija Sucheta; Shetty Shashikant; Vijayalakshmi P (Indian Journal of Ophthalmology, 2007)
Duane′s retraction syndrome (DRS) includes changes in palpebral fissure width along with restriction of ocular motility. Bardet Biedl syndrome (BBS) includes presence of retinitis pigmentosa (RP) with obesity, mental retardation, polydactyly and renal abnormalities. We report a case of rare association of DRS with BBS in a seven-year-old child. The ocular motility examination revealed left DRS with esotropia. Fundus examination revealed findings characteristic of an atypical retinitis pigmentosa. The electro-retinogram waveforms were extinguished both for rods and cones. He was diagnosed as a case of BBS on the basis of the ophthalmological findings plus association with the systemic features of obesity, polydactyly, hypogonadism, mental retardation and renal abnormalities. This case gives further evidence of the fact that BBS may be associated with abnormalities of eye movements.